The impact of big data and big data analytics in external auditing procedures - Santos, Joana Pedrosa (2019)
Companies that can effectively utilize big data, on average, have a 5 to 6 per cent higher gain in productivity (Brynjolfsson et al., 2011). This fact is not going unnoticed by the auditor’s community that has been implementing data analytic tools in their projects. The aim of this working project, written in the form of a direct research on EY assurance department, is to understand this impact on auditing procedures. Facilitators and obstacles are the factors that determine how big data and data analytics usage will evolve in audit practice, with leadership commitment identified as the most significant facilitator and aversion to change as potentially the greatest obstacle.